(3GdMeGjI GdLfGFjI ddMb ai GdTQa hGdGYJHGQ (B: s (3OQGSI ebGQfI (B/ s - (3YdGA GdOjf Ydi aGVd GdSjOs; (3GMeO YhV HdGds; (3eMehO fLjH MSfi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2004)
(3JJNP eSGdI GdOaY HGdMbjbI ai GdJTQjYGJ GdebGQfI GJLGgjf Gh dgeG GHGMI GdOaY HGdMbjbI ef NdGd GKHGJ MbjbI GdaYd GdeSfO (B: (3hgi HPdc JJNP GdOaY HGdMbjbI eHOC YGeG (B: (3hKGfjgeG JLYd GdOaY HGdMbjbI eSCdI GSJKfGFjI ai LQGFe GdTQa hGdGYJHGQ (B: (3hdYd GdGJLGg GdGhd jJab eY GdTQjYI GdGSdGejI ai JHfi gPG GdeHOC (B: (3GeG GdGJLGg GdKGfi aEfg jJab hJTQjYfG GdhWfi ai bUQ GHGMI GdOaY HGdMbjbI ai GSJKfGA Vjb eeG jLYdfG fba hbaI LGOI dG jbdd ef GgejJgG Gf acQ GdZjQ djS MLI YdjfG (B: (3dCf dacQ GdZjQ SfOG jUYH GdGdJaGJ Yfg (B: (3hcPdc aEf Mce GdTQjYI GdGSdGejI bjeI QhMjI hOSJhQjI dG jecf JLGgdgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2004s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B501-519s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjYGJ GdebGQfIs; (3GdMeGjI GdLfGFjIs; (3GdTQjYI GdGSdGejIs; (3GdGYJHGQs; (3GdTQas; (3GdbPas; (3Mb GdfbOs; (3GdHdGZ GdcGPHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs